GA3 Concentration and Application Timing for Enhanced Parthenocarpy Induction and Fruit Quality in Cucumber (Cucumis sativus L.) - Elvina Diah Mar’atussolihah; Felicitas Deru Dewanti; Rossyda Priyadarshini (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
Cucumber is a high-value horticultural crop for which stable fruit set and seedless quality are increasingly in demand in intensive production systems. Parthenocarpy induction using gibberellic acid (GA3) offers a practical strategy to enhance yield stability and market preference under limited pollination conditions. This study aimed to evaluate the independent and combined effects of GA.3 concentration and application timing on parthenocarpy success, yield components, and fruit quality in greenhouse-grown cucumber. A factorial completely randomised design tested four GA3 concentrations (0, 100, 200, 300 ppm) and three application timings (pre-anthesis, anthesis, post-anthesis) with three replications. Results revealed that both concentration and timing significantly affected Fruit Set percentage, while their interaction was not significant. Fruit Set increased progressively from control (70.21%) to 300 ppm (87.81%), with anthesis application producing the highest mean Fruit Set (86.97%). Higher GA2 levels (200–300 ppm) improved fruit weight, diameter, length, and flesh thickness, while substantially reducing seed number. The findings indicate a nonlinear dose–response pattern with a tendency toward saturation at higher concentrations. Optimizing GA3 concentration and synchronizing its application with anthesis enhances parthenocarpy efficiency, yield, and commercial fruit quality in cucumber production systems. Contribution to Sustainable Development Goals (SDGs):SDG 2: Zero HungerSDG 8: Decent Work and Economic GrowthSDG 9: Industry, Innovation, and InfrastructureSDG 12: Responsible Consumption and ProductionSDG 13: Climate Action